Topical cannabidiol (CBD) in skin pathology – A comprehensive review and prospects for new therapeutic opportunities - Lehlohonolo Makhakhe (South African Family Practice)
Humans have utilised cannabis products in various forms throughout the recorded history. To date, more than 500 biologically active components have been identified in the plants of the Cannabis genus, amongst which more than 100 were classified as phytocannabinoids (exocannabinoids). The plant genus Cannabis is a member of the plant family Cannabaceae, and there are three primary cannabis species which vary in their biochemical constituents: Cannabis sativa, Cannabis indica and Cannabis ruderalis. There has been a growing level of interest in research on the topical usage of a cannabis-based extract as a safer and more effective alternative to the usage of topical corticosteroids in treating some dermatoses. Together with the discovery of the cannabinoid receptors on the skin, it has been further illustrated that topical cannabis has anti-inflammatory, anti-itching, analgesics, wound healing and anti-proliferative effects on the skin.